Serum Prolactin in Advanced Chronic Liver Disease - Ress, C.; Maeser, P.-A.; Tschoner, A.; Loacker, L.; Salzmann, K.; Staudacher, G.; Melmer, A.; Zoller, H.; Vogel, W.; Griesmacher, A.; Tilg, H.; Graziadei, I.; Kaser, S. (Hormone and Metabolic Research, 2014)
Hyperprolactinemia is a frequent endocrine disorder with well known harmful effects on the reproductive system and bone metabolism. Besides prolactinomas several drugs and disorders such as renal failure and hypothyroidism have been shown to cause hyperprolactinemia. Based on former studies, liver cirrhosis has also been suggested to cause hyperprolactinemia, while mechanisms have not been identified yet. In this study, we set out to investigate the prevalence and predictors of hyperprolactinemia in 178 patients with liver cirrhosis of different etiologies. Eighteen out of 178 patients – 7 females and 11 males – displayed elevated serum prolactin levels. When patients were excluded who suffered from co-morbidities or took medication that are discussed to potentially interfere with prolactin metabolism, only 3 males displayed increased serum prolactin levels. Prolactin levels were similar in patients with liver cirrhosis of different etiologies. Our data suggest that hyperprolactinemia is not commonly found in patients with liver cirrhosis, but is mostly associated with intake of drugs or presence of comorbidites which are known to potentially cause hyperprolactinemia. We thus hypothesize that in contrast to former studies liver cirrhosis is not a common cause of hyperprolactinemia and that in the absence of co-morbidities or drugs that are known to potentially increase prolactin levels, marked hyperprolactinemia needs further investigation in patients with liver cirrhosis.
Keywords: prolactin; liver cirrhosis; Child–Pugh score